Technology and operational sensitivity assessment for hypersonic endurance flight vehicles. (March 2015) - Chudoba, B.; Coleman, G.; Oza, A.; Gonzalez, L.; Czysz, P.A.
Abstract: In an effort to increase the air-breathing endurance capability of current hypersonic research aircraft (i.e. X-43, 7 seconds; X-51, 5 minutes), the authors have explored the technical and operational solution space for a 30 minute cruise endurance demonstrator operating in the Mach 6 to Mach 8 speed regime. The focus of this activity has been on exploration of the available solution space through a unique screening process to assess the implication and interplay between the (a) mission, (b) baseline vehicle, and (c) operational scenarios. This study concludes that an air-launched, liquid hydrogen fuelled, 30 minute duration Mach 6 demonstrator (with 10 min Mach 8 capability) provides the largest feasible solution space of the trades examined (i.e. largest design margins, lowest technical risk) when compared to a kerosene-powered equivalent.